2018
DOI: 10.1111/wej.12435
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the novel infiltration model with other infiltration models

Abstract: Variability in infiltration characteristics of soils creates need for selection of appropriate infiltration model. Recently, a novel infiltration model was proposed and reported to perform excellently in estimating infiltration rate of soils of Kurukshetra, India, however, this model need to be tested for its reliability at global level. In this regard, the present study analyses the reliability of the novel model based on infiltration database comprising of 16 data sets from different parts of the world to ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Thus, they found that the Novel model was suitable for sandy loam, loam and clayey loam. In this regard, it may be inferred that the Novel model may accurately predict the infiltration rate in loamy soils (Zakwan 2020).…”
Section: Determination Of Infiltration Model Parametersmentioning
confidence: 96%
“…Thus, they found that the Novel model was suitable for sandy loam, loam and clayey loam. In this regard, it may be inferred that the Novel model may accurately predict the infiltration rate in loamy soils (Zakwan 2020).…”
Section: Determination Of Infiltration Model Parametersmentioning
confidence: 96%
“…One-dimensional vertical infiltration simulation in the soil has been a heated and productive topic of research for domestic and overseas experts and the simulation formulas could be classified as theoretical models such as the Green-Ampt infiltration model or Philip formula, semi-empirical models such as the Horton and Holtan models, and empirical models such as the Kostiakov and Huggins-Monke models [20][21][22][23]. Zhen et al (2016) [9] validated that the water infiltration process in homogeneous soil can be effectively fitted by both Philip and Kostiakov infiltration models.…”
Section: Simulation Of Water Infiltration In Homogeneous Soilmentioning
confidence: 99%
“…(Kim et al, 2016;Pandey et al, 2018;Sun et al, 2019;Alizadeh, 2019). In short, low water quality can cause problems, indicating the effects of seepage, in ltration, and quality of the ecosystem (Alizadeh et al, 2019;Zakwan, 2019 ;Keshtkar et al 2013). The essential role of rivers is in ecosystems based on the environmental role.…”
Section: Introductionmentioning
confidence: 99%